PEMANFAATAN CERITA RAKYAT SEBAGAI BAHAN PENDUKUNG PEMBELAJARAN BIPA DI ASEAN - Muhammad Yasif Femi Mifthah (Multilingual, 2021)
AbstractCultural issues often become learning matters in the Indonesian as a foreign language (BIPA) program. In fact, ASEAN learners also face the learning experience. Hence, the use of folklores is an option to overcome the issue. The famous folklores from the learners’ country were considered on choosing Indonesian folklores as a learning material for BIPA learners. It regards the Gagne schema theory that emphasizes on the learner’s insight as the fundamental of understanding. This study elaborates the use of proper Indonesian folklores in learning BIPA, especially for ASEAN learners.  The comparative literature focusing on the Aarne-Thompson motif-index was used to compare Indonesian folklores to target BIPA learners’. The result depicted that some of ASEAN folklores are identical to Indonesian folklores. The Indonesian folklores like ‘Ande-Ande Lumut’ or ‘Bawang Merah dan Putih’, ‘Si Kancil dan Pak Tani’ or ‘Raja Palsu (Petualangan si Kancil)’ have similarities in the Cinderella motif and the trickster motif to Thailand folklores like ‘Kao and the Golden Fish’ and ‘Xiang Miang and The Snail’; Vietnam folklores like ‘The Story of Tam and Cham’ and ‘The Peasant, ‘The Buffalo, and The Tiger’; Filipina folklores like ‘Abadeha’ and ‘Pilandok and the Sumusong-sa-Alongan’; and Malaysia folklores like ‘Bawang Merah dan Putih’ and ‘Kerbau and Buaya’. In brief, the Indonesian folklores having similarities to target learners’ can be considered as a cultural material in learning BIPA, especially for ASEAN learners.Key words: folklores, motif-index, BIPA. AbstrakMeski di ASEAN sekalipun, faktor budaya sering menjadi hambatan dalam pembelajaran BIPA. hal itu dapat dijembatani dengan memanfaatkan cerita rakyat Indonesia yang memiliki kesamaan dengan cerita dari negara asal pemelajar. Mengacu teori skema strategi pembelajaran bahasa asing Gagne, pembelajaran BIPA di ASEAN perlu mempertimbangkan dengan serius faktor budaya dalam pemilihan/penentuan bahan ajar. Kajian ini menawarkan teknik pemilihan cerita rakyat Indonesia yang akan digunakan sebagai bahan ajar BIPA dengan memanfaatkan metode sastra bandingan dan teori kesamaan tipe/indeks motif Aarne dan Thompson. Hasil kajian menunjukkan bahwa cerita rakyat di ASEAN identik dengan tipe/motif Cinderella dan the trickster. Cerita rakyat Indonesia dengan tipe Cinderella seperti; ‘Ande-Ande Lumut’ atau ‘Bawang Merah dan Putih’, dan cerita bertipe the trickster seperti; ‘Si Kancil dan Pak Tani’, atau cerita ‘Raja Palsu’ (Petualangan Si Kancil) dapat dijadikan bahan ajar BIPA di ASEAN karena memiliki kesamaan dengan cerita rakyat Thailand; ‘Kao and the Golden Fish’ dan ‘Xiang Miang and The Snail’, cerita rakyat Vietnam; ‘The Story of Tam and Cham’ dan ‘The Peasant, the Buffalo, and the Tiger’, cerita rakyat Filipina; ‘Abadeha’ dan ‘Pilandok and the Sumusong-sa-Alongan’ dan cerita rakyat Malaysia; ‘Bawang Merah dan Putih’ dan ‘Kerbau dan Buaya’.Kata-kata kunci: Cerita rakyat, tipe, motif, bahan ajar, BIPA